High-Performance Wireless Piezoelectric Sensor Network for Distributed Structural Health Monitoring - Shang Gao; Xuewu Dai; Zheng Liu; Guiyun Tian (International Journal of Distributed Sensor Networks)
This paper presents the development of a newly designed wireless piezoelectric (PZT) sensor platform for distributed large-scale structure health monitoring, where real-time data acquisition with high sampling rate up to 12.5 Msps (sample per second) and distributed lamb-wave data processing are implemented. In the proposed wireless PZT network, a set of PZT transducers are deployed at the surface of the structure, a lamb-wave is excited, and its propagation characteristics within the structure are inspected to identify damages. The developed wireless node platform features a digital signal processor (DSP) of TMS320F28335 and an improved IEEE 802.15.4 wireless data transducer RF233 with up to 2 Mbps data rate. Each node supports up to 8 PZT transducers, one of which works as the actuator generating the lamb-wave at an arbitrary frequency, while the responding vibrations at other PZT sensors are sensed simultaneously. In addition to hardware, embedded signal processing and distributed data processing algorithm are designed as the intelligent “brain” of the proposed wireless monitoring network to extract features of the PZT signals, so that the data transmitted over the wireless link can be reduced significantly.